(untitled) (Environment & Health, 2017)
Objective: In the article we raised a question of the relevance of the hygienic approach to the assessment of the solatenol based combined fungicide application safety to human and environment and its effect on the sanitary regime of water bodies for domestic-drinking, cultural-household purposes. Results: Hygienic studies of solatenol influence on the processes, taking place in water of the model water bodies, were carried out. The amount of studied active substance, affecting the biochemical oxygen consumption, the dynamics of the saprophyte microflora, the nitrogen content of ammonia, the nitrogen of nitrites and nitrates, was determined, as well as the content of dissolved oxygen in water and the active reaction of water (pH).. Statistical calculations of the arithmetic mean and the error of mean were also performed. As a result of the conducted studies, it was established that concentration of solatenol in water at 0.0007 mg/dm3 (the limiting index is the effect on nitrification processes) is the threshold by the general sanitary index of hazard. Conclusions: The proposed value was taken into account in the development of the hygienic standard of solatenol maximum permissible concentration in water of the bodies for domestic-and-drinking, cultural-and-household purposes.